2023
DOI: 10.1038/s41467-023-36586-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of mRNA stability modulates transcriptional memory and facilitates environmental adaptation

Abstract: Transcriptional memory, by which cells respond faster to repeated stimuli, is key for cellular adaptation and organism survival. Chromatin organization has been shown to play a role in the faster response of primed cells. However, the contribution of post-transcriptional regulation is not yet explored. Here we perform a genome-wide screen to identify novel factors modulating transcriptional memory in S. cerevisiae in response to galactose. We find that depletion of the nuclear RNA exosome increases GAL1 expres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…mRNA decay and translation) to priming and PSM. A recent report using yeast cells showed for the first time that both nuclear and cytoplasmic mRNA degradation contribute to gene expression memory (Li et al, 2023), but a similar role for mRNA decay in plants has not yet been explored. However, it has been reported that one of the fastest ways (within minutes) for plants to adapt their genetic program to rapidly fluctuating temperatures is to modulate global mRNA populations by inducing decay processes (Merret et al, 2013; Crisp et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…mRNA decay and translation) to priming and PSM. A recent report using yeast cells showed for the first time that both nuclear and cytoplasmic mRNA degradation contribute to gene expression memory (Li et al, 2023), but a similar role for mRNA decay in plants has not yet been explored. However, it has been reported that one of the fastest ways (within minutes) for plants to adapt their genetic program to rapidly fluctuating temperatures is to modulate global mRNA populations by inducing decay processes (Merret et al, 2013; Crisp et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple mechanisms control mRNA decay in response to environmental changes, for example, by destabilizing specific mRNAs in response to RNA binding proteins association 4 , by regulating the activity of proteins involved in mRNA decay 5,6 , or through co-translational mRNA decay 7,8,9 . A general process where the translation process modulates mRNA decay is the coupling between the demand of tRNAs by translating ribosomes and the available supply of charged tRNAs (codon optimality) which has been shown to regulate mRNA stability 10,11,12,13 .…”
Section: Introductionmentioning
confidence: 99%